Fifty years of creativity, crisis, and cancer in Uganda. Issue 3 (1st September 2016) - Mika, Marissa
Abstract: This article tells the story of the Uganda Cancer Institute over the past 50 years. I discuss the fundamental dynamism of research collaborations and the ways in which they bring vital yet partial investments in improving the capacity of medical facilities in sub-Saharan Africa. I explore the ways in which patient populations and the needs of caretakers themselves shape research collaborations. I also show how extreme oscillations in the capacity to conduct oncology research and provide care were (and are) tied not only to shifting international research priorities, but also to broader upheaval and periods of stability in Uganda since independence in 1962. Rather than dwelling on the debris, ruins, or an emptying of capacity in the health sector in Africa, this article highlights how this experimental infrastructure in East Africa not only survived, but also fundamentally shaped a culture of care and oncology practice that lived on.